1986
DOI: 10.1071/ar9860425
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vegetative and reproductive development in the mango in northern Australia

Abstract: Vegetative and reproductive growth was recorded on mature mango trees (cultivar Kensington) over two years in northern Australia. There were four vegetative growth flushes during each year, but not all shoots grew during each flush. Observations on the flowering of shoots of known age showed that the older shoots produced most inflorescences. Microscopic examination of terminal buds showed that floral initiation occurred within a month of the commencement of the flowering flush under these tropical conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 8 publications
(12 reference statements)
2
8
0
Order By: Relevance
“…These results are in line with the finding of Thakur et al (2000), Hammam et al, (2001), El-Wakeel et al, (2006, Scholefield et al (2006), Reddy and Reddy (2009), El-Agmey (2010) Hagage (2010) and Serry (2010)…”
Section: Seed Peel and Pulp Percentagesupporting
confidence: 92%
“…These results are in line with the finding of Thakur et al (2000), Hammam et al, (2001), El-Wakeel et al, (2006, Scholefield et al (2006), Reddy and Reddy (2009), El-Agmey (2010) Hagage (2010) and Serry (2010)…”
Section: Seed Peel and Pulp Percentagesupporting
confidence: 92%
“…This suggests that although organ development is closely related to temperature (Bonhomme, 2000;, vegetative and reproductive development in mango is, for a large part, governed by endogenous factors and not just by environmental cues. In this way, some studies on mango showed that an old GU bursts earlier (Scholefield et al, 1986) and has a higher occurrence of flowering (Scholefield et al, 1986;Davenport, 2000;Jannoyer and Lauri, 2009) than a more recent GU. It has also been shown that reiterated complexes, which are repetitions of parts or of the whole sequence of the tree architectural model (Hallé et al, 1978), have a phenology that differs from the rest of the tree (Goguey, 1997).…”
Section: Introductionmentioning
confidence: 94%
“…Eight weeks after flowering, 30 trees had branches thinned to a single fruit and girdled to isolate the fruit with 30, 60 or 120 leaves (hereafter referred to as treatment 30, 60 or 120). It was expected that the leaf:fruit ratio would remain constant within the treatments through to harvest as vegetative growth does not occur on fruiting mango terminals during fruit ontogeny (Scholefield et al, 1986). Branches were girdled by making a 10-15 mm wide cut through the bark to the cambium.…”
Section: Field Treatmentsmentioning
confidence: 99%